2001
DOI: 10.1177/0145445501252007
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Token Economy and Methylphenidate on Attentive and Disruptive Behavior during Sports with Adhd-Diagnosed Children

Abstract: Three children diagnosed with attention deficit hyperactivity disorder (ADHD) participated in a summer program designed to evaluate the influence of stimulant medication and a token economy on attentive and disruptive behavior during kickball games. Attentive and disruptive behavior were assessed using an interval coding system, and daily ratings on the ADHD Index of the Conners Teacher Rating Scale-Revised were also obtained. A multielement reversal design was used, and the results indicated that both interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 28 publications
5
31
1
2
Order By: Relevance
“…In one study (Kolko et al, 1999), medication was superior to BPI in an unstructured enrichment setting (ES ¼ À.3.39), whereas other studies indicated a benefit of BPI over medication in recreational settings (ES ¼ 2.56, Reitman et al, 2001;ES ¼ 5.71, Hupp et al, 2002).…”
Section: Effect Sizesmentioning
confidence: 96%
See 1 more Smart Citation
“…In one study (Kolko et al, 1999), medication was superior to BPI in an unstructured enrichment setting (ES ¼ À.3.39), whereas other studies indicated a benefit of BPI over medication in recreational settings (ES ¼ 2.56, Reitman et al, 2001;ES ¼ 5.71, Hupp et al, 2002).…”
Section: Effect Sizesmentioning
confidence: 96%
“…Since the initial task force review, however, there have been two large between-group Pelham, Burrows-MacLean et al, 2008a), five large crossover Fabiano 196 PELHAM AND FABIANO et al, 2004;Kolko et al, 1999;Pelham, BurrowsMacLean et al, 2008b;Pelham, Burrows-MacLean et al, 2005), and a number of well-controlled, singlesubject studies (e.g., Coles et al, 2005;Hupp et al, 2002;Reitman, Hupp, O'Callaghan, Gulley, & Northup, 2001) that report on the effect of BI for peer problems in recreational settings-typically STPs. In addition, the STP was a component of the MTA study.…”
Section: Behavioral Peer Interventionsmentioning
confidence: 99%
“…The main mechanism of the RCT training is improvement of abilities for self-control (Gerber et al 2011;Northup et al 1999;Pelham et al 1997;Reitman et al 2001;Tamm and Carlson 2007). The training consists of four units of 30 min each during which patients with ADHD are instructed to perform arithmetic tasks and write a dictation.…”
Section: Effect Of Response Cost and Token Training Programmentioning
confidence: 99%
“…There is increasing evidence that the RCT approach is effective in the treatment of ADHD. In previous studies, RCT treatment programs were able to reduce symptoms of ADHD and improve neuropsychological performance (Northup et al 1999;Pelham et al 1997;Reitman et al 2001;Tamm and Carlson 2007). Recently, we applied the RCT approach within the scope of summer camp training in children with ADHD and demonstrated that the RCT training improved the clinical course of ADHD at 2 years follow-up, reduced performance variability and improved attention in these patients, as well as positively influenced their quality of life (Gerber et al 2011;Toussaint et al 2011).…”
mentioning
confidence: 97%
“…With notable exceptions, only a few studies have examined use of stimulant medication with young children engaged in recreational activities (Pelham et al, 1990(Pelham et al, , 1999Reitman et al, 2001). As would likely occur in outpatient treatment, medication dosages were determined based on response to academic tasks.…”
Section: Discussionmentioning
confidence: 99%